Pola Interaksi Sosial di Warung (Studi Kasus pada Interaksi Sosial di Warung Sembako di Kelurahan Pulogebang Kota Jakarta Timur) - Rizki Rahman; Vera Octavia (Jurnal Studi Ilmu Sosial dan Politik, 2022)
Purpose: The purpose of this study was to determine patterns of social interaction in stalls and to determine the behavior of buyers. Research Methodology: The research method used is descriptive qualitative method. Data collection was carried out by participant observation, namely researchers involved in direct interactions with data sources in the field and by observing daily activities at four stalls in Pulogebang Village and researchers also conducted interviews with eight informants. Results: The results of this study show that social interactions that occur in stalls are not only in terms of buying and selling, but there are other conversations outside the context of buying and selling. The interactions that occur in the warung can be associative (cooperation, accommodation, assimilation) and dissociative (competition, contradiction, conflict). As well as the behavior of customers in the Pulogebang Village stalls is a positive behavior in social life. Contribution: This research is expected to be useful for the development of sociology, and can add to the knowledge of sociologists about social interaction, besides that it can help stall visitors and sellers be aware of the importance of good social interaction with the community.